Perbaikan Penanganan Pascapanen Asparagus (Asparagus officinalis) dari Petani di Kecamatan Petang hingga Pengecer di Denpasar - Arista Pradnyani, Luh Gede; Harsojuwono, Bambang Admadi; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p04, 2019)
The aim of this study were to determine the number of asparagus distribution lines and types of distribution, find out the impact of postharvest handling and to determine the impact of improvements postharvest on asparagus damage from farmers in Petang district to retailers in Denpasar. Postharvest improvements in this study by replacing the packaging using styrofoam box and placing the asparagus vertically. There are three lines in the distribution of asparagus. The first line (Farmers ? Cooperative ? Suppliers ? Retailer ? Consumer), line II (Farmer ? Middleman ? Suppliers ? Retailer ? Consumer) and line III (Farmer ? Middleman ? Suppliers ? Consumer). Postharvest handling includes harvesting, cleaning, cutting, sorting, grading, binding, storage, packaging, distribution and displaying. The impact of handling postharvest loss in the sorting stage at the farmers level is 2.5% (non significant), cooperative level is 1.8% (non significant), middleman level is 4% (insignificant), supplier level is 5.4% (significant) and retailers level is 6.69% (significant). Postharvest improvement by changing the packaging could reduce the level defect of asparagus to 7.81%.   Keywords : asparagus, styrofoam packaging, CSAM, postharvest handling, improvements